Characteristic Zero Resolution (Lascoux Resolution) of Weyl Module in the Case of the Skew- Partition (11, 7, 5)/ (1, 1, 1) - Abd-Alridah, Shaymaa N.; Hassan, Haytham R. (Iraqi Journal of Science, 2023)
In this paper, the terms of Lascoux and boundary maps for the skew-partition (11,7,5) / (1,1,1) are found by using the Jacobi-Trudi matrix of partition. Further, Lascoux resolution is studied by using a mapping Cone without depending on the characteristic-free resolution of the Weyl module for the same skew-partition.